Customer resistance to churn in a mature mobile telecommunications market. (9th January 2020) - Kim, Seungyeon; Chang, Younghoon; Wong, Siew Fan; Park, Myeong-Cheol
Effective customer retention is critical for company survival, especially in a mature mobile telecommunications market. To build on customer retention research, we propose an integrative model capturing the dual relational mechanisms that explain customer resistance to churn. We empirically test the model using data from 815 subscribers who have stayed with their mobile network operators for more than three years. The results show that two contrasting mechanisms, dedication-based and constraint-based relationships, simultaneously determine customer resistance to churn. The constraints of procedural, financial, and relational costs significantly influence perceived risk, while dedication factors of economy-based and identification-based trust significantly influence commitment.